2016
DOI: 10.3748/wjg.v22.i22.5183
|View full text |Cite
|
Sign up to set email alerts
|

miR-106b promotes cancer progression in hepatitis B virus-associated hepatocellular carcinoma

Abstract: The data obtained in the present study suggests that HBx enhances miR-106b transcription to promote tumor progression in HBV-associated HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…In our study, we found that CTC‐specific miR106b was positively related to the expression level of vimentin in CTCs. It has been reported that overexpression of miR‐106b was observed in a variety of human tumors, which plays an oncogenic role in tumor progression and prognosis, including colorectal cancer , gastric cancer , hepatocellular carcinoma , glioma tumors , renal cell carcinoma , and head and neck squamous cell carcinomas . MiR‐106b plays a functional role in promoting proliferation, migration, and invasion of cancer cells both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that CTC‐specific miR106b was positively related to the expression level of vimentin in CTCs. It has been reported that overexpression of miR‐106b was observed in a variety of human tumors, which plays an oncogenic role in tumor progression and prognosis, including colorectal cancer , gastric cancer , hepatocellular carcinoma , glioma tumors , renal cell carcinoma , and head and neck squamous cell carcinomas . MiR‐106b plays a functional role in promoting proliferation, migration, and invasion of cancer cells both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…All six members of the miR-17 family (miR-17, 20a, 20b, 93, 106a, and 106b) have been shown to function as onco-miRs in multiple malignancies (12,13,(31)(32)(33)(34)(35)(36)(37). As they share the same seed sequence, they likely target common genes and function redundantly.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the consistent decline of miR-199a/b-3p in HCC and its significant correlation with poor prognosis of HCC patients has been elucidated, suggesting miR-199a/b-3p as a potential HBV therapeutic target. Gao et al Several studies have suggested the role of HBx protein in miRNA expression during HBV infection [67,96,98,106]. For example, the recent study, conducted on 120 patients with HBV-related HCC, has shown that the expression of miR-106b was significantly higher in HBV-related HCC patients in comparison to non-HBV/non-HCV-related HCC patients and suggested that HBx enhances miR-106b transcription and therefore promotes tumor progression in HBV-related HCC [98].…”
Section: Hbv Mirna Biomarkersmentioning
confidence: 99%
“…Gao et al Several studies have suggested the role of HBx protein in miRNA expression during HBV infection [67,96,98,106]. For example, the recent study, conducted on 120 patients with HBV-related HCC, has shown that the expression of miR-106b was significantly higher in HBV-related HCC patients in comparison to non-HBV/non-HCV-related HCC patients and suggested that HBx enhances miR-106b transcription and therefore promotes tumor progression in HBV-related HCC [98]. Transfection with the HBx expression plasmid has been recently used in an additional study by Yu et al [114] to investigate HBx-related regulation of miR-19a, miR-122, and miR-223 in malignant hepatocytes.…”
Section: Hbv Mirna Biomarkersmentioning
confidence: 99%